On the Mechanism of Osmotic Protection of Erythrocytes. I. Model of Osmometer - Rudenko, S. V.; Shchetinina, E. M.; Volovelskaya, E. L. (Problems of Cryobiology and Cryomedicine, 2011)
The properties of simple model of osmotic balance in erythrocytes involving the contributions of intracellular electrolytes and non-ideal osmotic properties of hemoglobin were investigated. Analyzing this model we suggested two mechanisms that may take part in the rise of erythrocyte resistance to hypotonic media induced by different agents. One mechanism is associated with protecting release of intracellular electrolytes, in particular, chloride anions, the second one is associated with the change of intracellular osmolarity presumably due to degradation of hemoglobin tetramers into dimers with a simultaneous redistribution of intracellular electrolytes. The ways for experimental testing of the suggested mechanisms have been shown.